Application of Traditional Minangkabau Dance Techniques in Implementing Students' Self-Development at SMA Negeri 1 Matur - Tessa Makhmuddah; Ayuthia Mayang Sari (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe the application of traditional Minangkabau dance techniques to improve the dance ability of SMA Negeri 1 Matur students. This type of research is a qualitative research with a descriptive method. The researcher's own research instruments are assisted by supporting instruments such as stationery, cameras, and flash drives. Data collection techniques are carried out through literature studies, observations, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the application of basic techniques of traditional dance movements can be an effective model for the self-development of students' dance arts in improving the dance ability of students' creations at SMA N 1 Matur. The methods used in the self-development of the art of plate dance creations are demonstrations, lectures and practice methods. The application of basic techniques of traditional Minangkabau dance movements using the demonstration method can be proven effective in improving the dance ability of students' creations at SMA N 1 Matur. Teaching the basic movements of traditional dance is a strong foundation for developing a variety of creative dance movements. During the performance, it was also seen that the students' ability to dance creative dances in accordance with the dance techniques that had been taught was also increased. In addition, support from various parties and adjustments in the implementation of training are needed to achieve optimal results. These results support the research hypothesis and provide important implications for the development of dance programs in schools.